2019
DOI: 10.1016/j.addbeh.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of correspondence between self-reported substance use and urinalysis screening among a racially diverse cohort of young men who have sex with men and transgender women

Abstract: It is unknown if estimates of illicit drug use among young men who have sex with men and transgender women (YMSM/TW) may be biased due to historical distrust of research or reliable due to more accepting norms for use. Research is needed to examine the validity of drug use self-reports among YMSM/TW. Data came from an ongoing longitudinal study of YMSM/TW aged 16-29 living in Chicago (analytic N = 1029). Baseline urinalysis screens for marijuana, ecstasy, amphetamine, methamphetamine, cocaine, benzodiazepine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Similarly, our findings suggest that urine testing is more efficacious than hair testing in detecting benzodiazepines, validating just over half of self-reported use. To our knowledge, only one other validity study within the past several decades has included benzodiazepines in their analyses (Li et al, 2019). Though their findings were limited to sexual minorities, Li et al also reported a fair level of agreement between urine test results and self-report of benzodiazepine use.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, our findings suggest that urine testing is more efficacious than hair testing in detecting benzodiazepines, validating just over half of self-reported use. To our knowledge, only one other validity study within the past several decades has included benzodiazepines in their analyses (Li et al, 2019). Though their findings were limited to sexual minorities, Li et al also reported a fair level of agreement between urine test results and self-report of benzodiazepine use.…”
Section: Discussionmentioning
confidence: 93%
“…The sensitivity of the URDS is above 98%. Sensitivities for the URDS compared to TLC ranged from 96% for cocaine to > 99% for Opioids [ 24 ]. Urine samples were analyzed by laboratory in Rafsanjan University of Medical Sciences.…”
Section: Methodsmentioning
confidence: 99%
“…The weak reinforcing effect of benzodiazepines can lead to their abuse [10]; however, few studies have explored the use of sedatives/hypnotics in sexual minorities. A cohort survey in which 90.2% of the participants were gay and bisexual men demonstrated a 10.2% rate of the self-reported use of benzodiazepines in the past 6 months [11]. Another study indicated that frequent transactional sex was associated with benzodiazepine use for MSM of whom 92.1% were gay and bisexual men [12].…”
Section: Use Of Painkillers and Sedatives/hypnotics In Sexual Minoritiesmentioning
confidence: 99%